IMPROVING STUDENTS'WRITING ABILITY THROUGH WRITING TASKS OF THE SECOND YEAR STUDENTS AT SMAN 2 SIAKHULU KAMPAR DISTRICT - Sri Wahyuni (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
Writing is not a spontaneous product so that it needs to take much time for making in good one. Writing tasks present to help students to organize their idea, write their idea into paragraph or sentence, then revise their writing, and the last, publish their final writing. Thus, The obejctive of this research was to know whether there is a significant improvement on students' writing ability after using writing tasks espesially in Hortatory Exposition. The research design was pre-experimental research focusing on quantitative approach and involved 39 students of the second year students at SMAN 2 Siakhulu Kampar District, Riau, Indonesia as the samples. Cluster random sampling technique was used by the writer to take the sample. The technique of data collection was writing test. The data were gathered from the result of students' writing ability in pre-test and post-test. The research finding has shown that the alternative hypothesis was accepted. The amount of improvement made from the pre-test and post-test in the experimental group that taueht by writing tasks was 19.92 (51.07%). This improvement was also shown by the standard deviation of pre-test and post-test which was 0.75. it could be concluded that the use of writing tasks was effective in giving better result on improving students' writing ability of the second year students at SMAN 2 Siakhulu Kampar District.